Thiosaccharine disulfide: Synthesis, crystal structure, spectroscopic characterization and theoretical study - Ferullo, Ricardo (2013)
The title compound, (thiosaccharine disulfide), bis[1,10dioxide-2,3-dihidro-1,2-benzoisothiazol]disulfide,(tsac)2 has been synthesized and fully characterized by UV?Visible, IR, Raman, 1H and 13C NMR spectroscopy elemental analysis and structural X-ray crystallography. A DFT theoretical study has been performed and good agreement between experimental and theoretical values of structural parameters and vibration frequencies have been achieved.